THE INFLUENCE OF ORGANITAZIONAL CLIMATE AND WORK ENVIROMENT ON EMPLOYESS PERFORMANCE OF XTRANS BANDUNG - Juriansyah, Soleh Fatwa; Deanda, Ferdyan Almer; , Rina; Rahayu, Beni; PamungkasMa, Hardian; Rachmawati, riana (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study reveals that there is a gap between Organizational Climate and Work Environment on the performance of Xtrans Bandung employees. This study aims to determine whether the Organizational Climate and Work Environment on the performance of Xtrans Bandung employees. The factors tested in this study were Organizational Climate and Work Environment as independent variables, while performance as the dependent variable. The research method used is descriptive method, with data collection techniques through observation and distributing questionnaires. The population in this study were employees of Xtrans Bandung with a sample of 144 respondents. The data analysis used multiple linear regression analysis at a significant level of 5%. The program used is SPSS 25. The results showed that the variables of Organizational Climate and Work Environment have a significant effect on employee performance.